2021
DOI: 10.3390/cancers13061187
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Signature of Small Cell Lung Cancer after Treatment Failure: The MCM Complex as Therapeutic Target

Abstract: Small cell lung cancer (SCLC) is a highly aggressive cancer, and patients who become refractory to first-line treatment have a poor prognosis. The development of effective treatment regimens is urgently needed. In this study, we identified a gene expression signature of SCLC after treatment failure using SCLC clinical specimens (GEO accession number: GSE162102). A total of 1,136 genes were significantly upregulated in SCLC tissues. These upregulated genes were subjected to KEGG pathway analysis, and “cell cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Recent studies by Sanada et al [ 44 ] have shown that siRNA-mediated MCM4 knockdown attenuates the invasiveness of lung adenocarcinoma cells. In addition, their team also confirmed that siRNA-mediated MCM4 knockdown enhanced the sensitivity of SCLC cells to cisplatin [ 45 ], suggesting that MCM4 could be used as a therapeutic target for SCLC.…”
Section: Discussionmentioning
confidence: 94%
“…Recent studies by Sanada et al [ 44 ] have shown that siRNA-mediated MCM4 knockdown attenuates the invasiveness of lung adenocarcinoma cells. In addition, their team also confirmed that siRNA-mediated MCM4 knockdown enhanced the sensitivity of SCLC cells to cisplatin [ 45 ], suggesting that MCM4 could be used as a therapeutic target for SCLC.…”
Section: Discussionmentioning
confidence: 94%
“…The MCM proteins have been shown to be highly expressed in malignant cancers cells as well as pre-cancerous cells that are undergoing malignant transformation [89]. MCM2 has been shown to be constantly expressed in rapidly growing cells of premalignant lung cancer [90]. MCM2 expression is also related to a higher mitotic index in breast cancer specimens [91].…”
Section: (Minichromosome Maintenance Complex)mentioning
confidence: 99%
“…Additionally, a series of recent studies correlated MCM expression with the development of hepatocellular carcinoma [92][93][94][95]. The MCM proteins are not highly expressed in somatic cells that have withdrawn from the cell cycle, making MCM proteins an ideal diagnostic marker for cancer and promising targets for the development of anti-cancer drugs [90,96].…”
Section: (Minichromosome Maintenance Complex)mentioning
confidence: 99%
“…It is encoded by MCM gene and its sequence is highly conserved. MCM protein family contains 10 monomers and has highly homology,which are closely related to the stability and accuracy of DNA replication.They participate in formation of complexes during the pre-replication of DNA, the initiation replication and prolongation of DNA [8,9]. MCM4 exists in the form of polymer in the early G1 phase of eukaryotic cell division and load onto the chromatin at the starting point of replication through CDC6(cell division cyclin 6) under the action of promoter and initiation recognition complex to form a pre-replication complex, which is the target site for replication inspection [10,11].…”
Section: Introductionmentioning
confidence: 99%